IMPACT OF THE DIFFERENT IRRIGATION SOURCES ON THE PLANTS DEVELOPMENT: A REVIEW (International Association of Biologicals and Computational Digest, 2022)
The effect of the five sources of the water on the growth of the plant. The five sources of irrigations are, Rain water,River water,Canal water,Tap Water, ground water. Some research has shown the quality of different water effect on the plant’s growth and development in an appropriate period of time. Some of the parameters like height & size of plant,number of flower and fruit was observed during this experiment time.During this review of water quality of different sources,we can find that water of the river and rainfall is a good source of irrigation and law ionic tap water we can prefer.Groundwater has salty expect to others, so it damagesof plant.
Keywords: Rain water,River water,Canal water,Tap water, ground water.